PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPS SISWA KELAS V DI SD - Febrianti, Fitri; Asran, Mastar; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the effect of the use of Problem Based Learning Model on the learning outcomes of Social Sciences of Class V Students of State Elementary School 22 Pontianak Barat. The experimental method design of this research is Quasi Experimental Design with Nonequivalent Control Group Design. The sample of research is VB class become experiment class and class become control class chosen by simple random sampling technique. The data collection tool used in the form of multiple choice amounted to 40 questions. Based on the data analysis, the average post test class experimental result is 62.29 and the average post test class test result is 56.83. The result of t test is obtained tcount 2,1008 and ttable Î± = 5% (with dk = 34 + 33 - 2 = 65) equal to 1,6699, which means tcount (2,1008)> ttable (1.6699), then Ha be accepted. It can be concluded that there is an effect of using Problem Based Learning model to the learning result of Social Sciences of Grade V students of State Elementary School 22 Pontianak Barat. From the calculation of the effect size of 0.539 (medium criterion). This means the use of Problem Based Learning model gives a good influence on the results of learning Social Sciences students in class V State Elementary School 22 Pontianak West.Â Keywords: Influence, Problem Based Learning, Learning Outcomes, Social Sciences